2022
DOI: 10.1136/bmjopen-2021-049955
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind cross-over pilot trial protocol to evaluate the safety and preliminary efficacy of long-term adaptive deep brain stimulation in patients with Parkinson’s disease

Abstract: IntroductionAfter several years of brain-sensing technology development and proof-of-concept studies, adaptive deep brain stimulation (aDBS) is ready to better treat Parkinson’s disease (PD) using aDBS-capable implantable pulse generators (IPGs). New aDBS devices are capable of continuous sensing of neuronal activity from the subthalamic nucleus (STN) and contemporaneous stimulation automatically adapted to match the patient’s clinical state estimated from the analysis of STN activity using proprietary algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This suggests individuals with PD could further benefit from aDBS. STN local field potential oscillations in a predefined beta band (13–30 Hz) are often proposed for adaptive (closed-loop) control in PD 2 , 17 , 18 based on the observation that resting subthalamic beta activity is elevated in the rigid/akinetic state and reduced when motor signs are alleviated by dopaminergic medication 19 or neurostimulation 20 . However, previous studies identified STN beta oscillations as control signals in the absence of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests individuals with PD could further benefit from aDBS. STN local field potential oscillations in a predefined beta band (13–30 Hz) are often proposed for adaptive (closed-loop) control in PD 2 , 17 , 18 based on the observation that resting subthalamic beta activity is elevated in the rigid/akinetic state and reduced when motor signs are alleviated by dopaminergic medication 19 or neurostimulation 20 . However, previous studies identified STN beta oscillations as control signals in the absence of stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The AlphaDBS system features advanced filtering technology for detecting local field potentials (LFPs) sensed through the DBS lead ( Arlotti et al, 2021 ; Marceglia et al, 2022 ). The implanted stimulator also utilizes a linear control algorithm that adjusts stimulation parameters according to the power in a selectable frequency band of LFPs.…”
Section: Alphadbs Is a New Implantable Closed-loop Clinical Neural In...mentioning
confidence: 99%
“…Dr. Rossi spoke about Newronika’s efforts in developing a closed-loop system for deep brain stimulation (DBS). He described both the capabilities of the device to records brain signals during stimulation delivery from the same DBS electrodes, that include the digital signal processing steps enabling adjustments of stimulation parameters in real-time (Marceglia et al 2022 ).…”
Section: Scientific Sessionsmentioning
confidence: 99%